Intranasal insulin affects brain, but not peripheral tissue, glucose uptake in lean, healthy men: a positron emission tomography study - Latva-Rasku, Aino; Laurila, Sanna; Karjalainen, Tomi; Klén, Riku; Löyttyniemi, Eliisa; Eskola, Olli; Nummenmaa, Lauri; Heni, Martin; Nuutila, Pirjo (American Physiological Society, 2026)
The brain has been suggested to regulate glucose metabolism in response to insulin in various tissues. As many of these findings have not been studied in humans, we aimed to assess the effects of intranasal insulin (INI) on brain and peripheral tissue-specific glucose uptake in lean, healthy men. On two separate visits, 10 volunteers received either 160 IU INI or placebo during a low-dose hyperinsulinemic, euglycemic clamp in a randomized, single-blinded, crossover design. Tissue glucose uptake was quantified using positron emission tomography (PET) and glucose analogue radiotracer 2-deoxy-2[18F]fluoro-d-glucose, with a dynamic scan starting from 40 min after INI. Tissue volumes and radiodensities were assessed with computed tomography. INI induced a global decrease in brain glucose uptake in all participants, with the magnitude of the effect correlating with the amount of visceral adipose tissue. In contrast, INI had no significant effect on skeletal muscle, liver, or adipose tissue glucose uptake. To conclude, a single dose of INI does not have a direct effect on peripheral glucose metabolism in healthy, lean men, but the previously reported hypothalamic response is accompanied by a global decrease in cerebral glucose metabolism.